2016
DOI: 10.1093/jisesa/iew057
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Semiochemicals Increase Trap Catch of Green Lacewings (Neuroptera: Chrysopidae) and Flower Flies (Diptera: Syrphidae) in Corn and Soybean Plots

Abstract: This study reports on the attractiveness of volatile chemicals to green lacewings (Neuroptera: Chrysopidae) and flower flies (Diptera: Syrphidae) as measured by catch on yellow sticky traps within corn [Zea mays L. (Cyperales: Poaceae)] and soybean [Glycine max (L.) Merr. (Fabales: Fabaceae)] plots. Green lacewings were attracted to eugenol-baited traps in two tests in soybean plots. Follow-up testing in corn showed that catch of green lacewings was enhanced when traps were baited with eugenol, its structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…(Neuroptera, Chrysopidae) (Lucchi et al, 2017). Further, flower flies (Diptera: Syrphidae) were found to be attracted to 2‐phenethyl alcohol in tests in corn and soybean plots (Hesler, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Neuroptera, Chrysopidae) (Lucchi et al, 2017). Further, flower flies (Diptera: Syrphidae) were found to be attracted to 2‐phenethyl alcohol in tests in corn and soybean plots (Hesler, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory and field tests, 2‐phenethyl alcohol was highly attractive to the common green lacewing, Chrysoperla carnea (Neuroptera, Chrysopidae) (Hesler, 2016; Zhu et al, 2005). A ternary blend of phenylacetonitrile, 2‐phenethyl alcohol and acetic acid attracted the common green lacewing, Chrysoperla plorabunda (Neuroptera, Chrysopidae) (El‐Sayed et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that using chemicals to guide C. pallens predation on pests could effectively improve their abilities to search for prey (Cui et al, 2015;Koczor et al, 2010). It is necessary to study the potential mechanism of their olfactory system for effective biological control (Hesler, 2016). A normalized transcriptome of C. pallens was sequenced by Li et al (2013), and a large number of candidate chemosensory genes were identified.…”
Section: F I G U R Ementioning
confidence: 99%
“…pallens predation on pests could effectively improve their abilities to search for prey (Cui et al, 2015 ; Koczor et al, 2010 ). It is necessary to study the potential mechanism of their olfactory system for effective biological control (Hesler, 2016 ). A normalized transcriptome of C .…”
Section: Introductionmentioning
confidence: 99%
“…Large bycatches of nontarget flies were sometimes unwittingly encountered in a study [8] that I conducted to evaluate responsiveness of arthropod natural enemies to various volatile chemicals among various field-crop habitats. Significant numbers of flies from three different families (Lauxaniidae, Chloropidae, and Anthomyiidae) were captured, and some captures represented potentially novel associations with volatile chemicals.…”
Section: Introductionmentioning
confidence: 99%